Pembelajaran Bermakna dalam Praktikum Kimia: Metode Campuran (Mixed Method) Menggunakan MLLIv2 - Erlina; Maria Ulfah; Eni Mayasari; Marisa (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to measure the extent of meaningful learning achieved by students during general chemistry laboratory activities. A descriptive quantitative design was employed with 126 participants, consisting of 51 Chemistry Education and 75 Biology Education students. Data were collected using the Meaningful Learning in the Laboratory Inventory (MLLIv2), which evaluates affective, cognitive, and affective–cognitive aspects. The data were analyzed and categorized into five levels from “very poor” to “very good.” The results showed that most students were in the “very good” category (81–100%) across all aspects, with smaller proportions in the “good” category (61–80%). No students were classified as “fair,” “poor,” or “very poor.” Chemistry Education students achieved slightly higher averages (affective = 91%, cognitive = 93%, affective–cognitive = 91%, overall = 92%) compared to Biology Education students (affective = 85%, cognitive = 89%, affective–cognitive = 89%, overall = 88%). These findings indicate that the laboratory effectively fostered meaningful learning by integrating cognitive understanding with affective engagement. The results also emphasize that meaningful learning is shaped not only by conceptual mastery but also by students’ emotional responses and their ability to connect laboratory experiences with academic and professional goals.